Development of a Microkinetic Model for the CO2 Methanation with an Automated Reaction Mechanism Generator - Kreitz, Bjarne; Wehinger, Gregor D.; Goldsmith, C. Franklin; Turek, Thomas (Computer Aided Chemical Engineering, 2020)
The automated reaction mechanism generator (RMG) is used to investigate the methanation of CO2 on the Ni(111) and Ni(211) surface. Linear scaling relations are applied for the thermochemistry of the adsorbates, which are compared to state-of-the-art electronic structure calculations and show a reasonable predictability. RMG discovers nearly the same amount of species and reactions for both facets. However, a reaction path analysis in a reactor simulation shows that the reaction pathways on both surfaces differ significantly, which is caused by the difference in the binding energy of the adsorbates. Reactor simulations reveal a lower methane production rate compared to experiments obtained in a Berty reactor with a Ni/Al2O3 catalyst, which is a result of a high surface coverage with CO⁎ and demands, therefore, the inclusion of a coverage dependent heat of formation of the adsorbates.